2011
DOI: 10.5534/kja.2011.29.2.91
|View full text |Cite
|
Sign up to set email alerts
|

Role of Phosphodiesterase Type 5 Inhibitor on Benign Prostatic Hyperplasia/Lower Urinary Tract Symptoms

Abstract: = Abstract =There is strong evidence from multiple epidemiological studies that benign prostate hyperplasia (BPH) induced lower urinary tract symptoms (LUTS) are correlated with erectile dysfunction (ED). Although a direct causal relationship is not established yet, four pathophysiological mechanisms can explain the relationship. These include alteration in and LUTS in subjects with ED. Basically PDE5 I with long half life is an appropriate candidate, therefore tadalafil and undenafil had been used to evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 63 publications
(50 reference statements)
1
7
0
Order By: Relevance
“…Porst and colleagues in 2009 reported similarly on the efficacy of tadalafil, with changes in IPSS, Qmax and PVR which were small and statistically insignificant [25, 26]. The IPSS findings from the present study were consistent with those from other studies of tadalafil 5 mg and tamsulosin 0.4 mg in Asian and non-Asian men with LUTS secondary to BPH [2732]. Oelke M et al, in a randomized control trial evaluating tadalafiland tamsulosin for LUTS secondary to BPH, suggested that monotherapy with tadalafilor tamsulosin resulted in a significant and numerically similar improvement in IPSS versus placebo, which is in contrast to our study [2].…”
Section: Discussionsupporting
confidence: 88%
“…Porst and colleagues in 2009 reported similarly on the efficacy of tadalafil, with changes in IPSS, Qmax and PVR which were small and statistically insignificant [25, 26]. The IPSS findings from the present study were consistent with those from other studies of tadalafil 5 mg and tamsulosin 0.4 mg in Asian and non-Asian men with LUTS secondary to BPH [2732]. Oelke M et al, in a randomized control trial evaluating tadalafiland tamsulosin for LUTS secondary to BPH, suggested that monotherapy with tadalafilor tamsulosin resulted in a significant and numerically similar improvement in IPSS versus placebo, which is in contrast to our study [2].…”
Section: Discussionsupporting
confidence: 88%
“…Many studies have demonstrated the effects of the nitric oxide pathway on symptoms related to lower urinary tract disorders [ 10 , 11 , 13 , 14 , 25 27 ]. In the study performed by Kim et al [ 10 ], four different reasons were proposed to explain how the nitric oxide pathway was related to lower urinary tract symptoms/BPH. In BPH, the reduction in nitric oxide bioavailability was related to BPH and LUTS.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, eNOS and nNOS played an important role in the nitric oxide pathway, and previous studies have shown that the berry mixture affects the stimulation or enhancement of the nitric oxide pathway [ 6 , 7 , 9 , 16 ]. In addition, there is evidence that the nitric oxide pathway and the related drug have an effect via controlling the ED and LUTS [ 10 , 11 , 13 , 14 , 25 , 28 ]. Kedia et al [ 25 ] observed that the enhancement of nitric oxide and the nitric oxide pathway signaling enzymes such as eNOS, nNOS, cGMP, cGK played an important role in smooth muscle contraction in human prostate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LUTS was an independent risk factor for ED [21] . Several mechanisms have been proposed to explain the relationship between LUTS and ED, including pelvic reduction in nitric oxide synthase (NOS)/nitric oxide (NO) [22,23] and autonomic nervous system over activity [22][23][24][25][26] . Abnormal up regulation of the Rho A/Rho kinase (ROCK) pathway, which mediates smooth muscle contraction, might also contribute to the lack of smooth muscle relaxation in the prostate, urethra, bladder neck, and penis [23][24][25] .…”
Section: Discussionmentioning
confidence: 99%